Relationship between Quality of Nursing Work Life with Nurse Job Satisfaction in Pilot Project of Nurse Clinical Career Implementation - Ineke Patrisia; Fransiska Sri Susilaningsih; Kurniawan Yudianto (Jurnal Keperawatan Padjadjaran, 2018)
Quality of nursing work life plays an important role and must be considered by a hospital organization for the achievement of nurse job satisfaction. The career ladder is one from the source of satisfaction according to Wexley & Yulk (2013) and will impact on service quality. The research method used correlational analysis with cross sectional approach. The number of samples in this study as many as 193 people. The results showed that in general, most of the respondents (98.4%) had a high quality of nursing work life and when viewed from career level category it was found that all clinical nurses 4 (100%) had high quality of work life and clinical nurses 1-3 (97.9%, 98.4%, 98.7%) most of respondents have high quality of work life. The results also showed that in general, most of respondents (79.3%) had nurses' job satisfaction and when viewed from career level category it was found that most of clinical nurses 1-4 (77.1%; 80.3%; 83.3%; 79.5%) were satisfied with their work. Indicators in the nurse's job satisfaction are the main priorities in the aspects of compensation, working conditions, recognition, independence. Indicators that need to be maintained by the management of Hasan Sadikin General Hospital Bandung are supervision technical, moral values, responsibility, advancement, co workers. The correlation between quality of nursing work life variable with nurse’s job satisfaction is weak, significant and unidirectional in the pilot project implementation of clinical nurse career ladder  in Hasan Sadikin General Hospital Bandung. Researchers expect the results of this study can be used as an evaluation for nursing management of Hasan Sadikin General Hospital Bandung. Further research is expected to be able to identify the relationship between the dimensions of the quality of nursing work life with the indicators of nurse’s job satisfaction.